James Joyce and Mario Vargas Llosa: Meeting on the Margins - Goodridge, Frankie (Cadernos de Literatura Comparada, 2022)
This study critiques two mainstream novelists known for their localities of Ireland and Peru as well as their long sojourns and major works set abroad. It argues that, contrary to popular, recent opinion regarding these seemingly abstruse and possibly elitist figures, both directly engage with the marginal aspects of both society and nature in intriguing and sensitive ways. Furthermore, these margins— as developed through consideration of a series of eclectic philosophical thinkers including Michel Foucault, Margarita Serje and Timothy Morton— are where the authors meet: where their writing converges. Comparison between the two hinges upon a philosophical understanding of these very margins. The writers, complex and irreducible, also seesaw between the terms that are almost always used to describe them: “modernist” and “realist”, “humorous” and “serious”, “local” and “global”, terms which I believe require renewed and nuanced consideration and recasting in the light of this comparison. Through a combination of close-readings and integrated theoretical analysis, I argue that Joyce and Vargas Llosa meet on the margins of: modern society, the environment, and their political contexts, producing some of the most timeless works of twentieth-century fiction as a result.